Detecting with X-ray absorption spectroscopy the modifications of the bonding structure of graphitic carbon by amorphisation, hydrogenation and nitrogenation - Gago, R; Jiménez, I; Albella, J.M (Surface science, 2001)
The bonding structure within distorted graphitic networks is a subject of great interest in connection with the study of fullerenes, nanotubes and amorphous carbon protective coatings. Here, we show that the distortion of the graphitic planes affects the near edge region of the X-ray absorption spectra. Different sets of graphitic carbon materials were studied, including crystalline graphite, sputtered graphite, hydrogen-free amorphous carbon (a-C) grown by physical vapour deposition (PVD) methods, hydrogenated a-C grown by chemical vapour deposition methods, and graphitic carbon nitride grown by PVD methods. Multiple bonding environments are detected, and are discussed in a comparative study.